Acquired Intermittent Pediatric Horner Syndrome due to Neuroblastoma. Issue 2 (March 2018) - Cohen, Liza M.; Elliott, Alexandra; Freitag, Suzanne K.
Abstract : A 3-month-old male developed intermittent left upper eyelid ptosis at the age of 1 month that was gradually increasing in frequency and duration. Examination revealed anisocoria and left upper and lower eyelid ptosis, consistent with a left Horner syndrome. Imaging showed a mass in the left superior posterior mediastinum, which was resected, and pathology was consistent with neuroblastoma. Eight months thereafter, the patient underwent left upper eyelid ptosis repair. Cases of infantile acquired Horner syndrome due to neuroblastoma are rare. To the authors' knowledge, there has only been one case described that presented with intermittent symptoms. The authors report the second case of intermittent acquired Horner syndrome due to neuroblastoma. This case demonstrates the importance of recognizing that Horner syndrome may present with subtle and intermittent symptoms. In a pediatric patient, one should maintain suspicion for neuroblastoma. Abstract : A 3-month-old male was presented with intermittent left upper eyelid ptosis and was diagnosed with acquired Horner syndrome due to neuroblastoma.